PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERNUANSA BUDAYA JAWA PADA MATERI GEOMETRI UNTUK MENINGKATKAN CRITICAL THINKING SISWA SD - Filawati Yunita; Sukmawarti Sukmawarti (Jurnal Inovasi Penelitian, 2023)
This study aims to develop a teaching material product in the form of a Student Worksheet with Javanese culture nuances on geometry material with the hope of helping students in learning activities and improving students' critical thinking. The method used in this study is the development of Research and Development (R&D) with the modification of the ADDIE development model through five stages including, analysis, design, development, implementation, and evaluation. The results showed that the LKPD with Javanese cultural nuances on the geometry material that was developed was feasible to be used as teaching material for mathematics learning geometry material, based on the validation of the classical percentage material expert of 85% with the "Very Appropriate" category, from the classical material expert the percentage of 82% with the category "Very Eligible", and the classical percentage of teacher validation is 96% with the "Very Eligible" category so that it can be concluded that the LKPD is in the good category and is suitable for use.